Solve for z y=-3z+2

Math
y=-3z+2
Rewrite the equation as -3z+2=y.
-3z+2=y
Subtract 2 from both sides of the equation.
-3z=y-2
Divide each term by -3 and simplify.
Tap for more steps…
Divide each term in -3z=y-2 by -3.
-3z-3=y-3+-2-3
Cancel the common factor of -3.
Tap for more steps…
Cancel the common factor.
-3z-3=y-3+-2-3
Divide z by 1.
z=y-3+-2-3
z=y-3+-2-3
Simplify each term.
Tap for more steps…
Move the negative in front of the fraction.
z=-y3+-2-3
Dividing two negative values results in a positive value.
z=-y3+23
z=-y3+23
z=-y3+23
Solve for z y=-3z+2

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top